Effectiveness of Giving Red Ginger Water Against Reducing the Intensity of Dysmenorrhea Pain in Young Women - Putri Isti Karomah; Diah Atmarina Yuliani (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2022)
Introduction: Dysmenorrhoea results from excessive amounts of prostaglandins. The chemical content of gingerol in red ginger can block prostaglandins so that it can reduce pain at the time of menstruation. Objective: Analyze the effectiveness of giving red ginger water against lowering the intensity of dysmenorrhea pain in young women. Methods: Quantitative research- pre-experiment design, Group Pretest, Posttest Design. The sample uses a non-probability sampling technique with a purposive sampling method. The instrument uses a Numeric Rating Scale (NRS) questionnaire. Results: Research shows an effectiveness between red ginger water and dysmenorrhoea where p value = 0.0001. Meanwhile, data analysis uses the Wilcoxon test with a confidence level of α = 0.05. Conclusion: There is an effectiveness between red ginger water and dysmenorrhoea. It is suggested that the findings of this study can be a solution to overcoming dysmenorrhoea by using a type of non-pharmacological therapy, namely the administration of red ginger water.